Reduction of heavy metal and microbial contaminants in septage via vermicomposting - Samaniego, Jessie O. (2009)
Septage or sludge from septic tank cntans heavy metals and pathogens that need to be treated. One treatment option is vermicomposting to convert septage into compost or soil conditioner. In this study, septage underwent vermicomposting process using african night crawler earthworms (Eudrilus euginae) for 60 days. Sawdust and cocopeat were added as bulking agents in different proportions to obtain C:N ratio conducive for optimum vermicomposting. The different mixtures (septage, septage+sawdust, and septage+cocopeat) were monitored for temperature, pH, and moisture content. Reduction of heavy metals (Zn. pB, Cu, Cr, Ni, Hg and Cd) was determined in all mixtures while validation was made by measuring the metal accumulation in the earthworms throughout the vermicomposting process. Pathogen removal was determined by regularly conducting coliform, Salmonella sp., and helmith ova analyses. The study showed that a significant decrease in the metals concentration in the mixture indicating that the earthworms can accumulate metal in their body tissues. In addition, the increase in temperature during the vermicomposting process reduced the number of coliform and Salmonella sp. Indeed, vermicomposting is a viable treatment for septage.
"October 2009."
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Sewage -- Purification -- Biological treatment; Vermicomposting; Sewage sludge -- Philippines -- Quezon City